Lipid nanoparticle-delivered IFNα2 activates Cxcl9 to increase T cell tumor recruitment to suppress lung metastasis - Yang Zhao; Valentyna Fesenkova; Kebin Liu; Dafeng Yang; Rafal Pacholczyk; Yi Tang; Dakota Poschel; Huidong Shi; Jin Xie; Kendra Fick; Nicholas Kerns; Zainab Tiamiyu; et al. (Journal for ImmunoTherapy of Cancer)
Background Emerging clinical and mouse tumor data indicate that tumor cells induce immune suppression in an anatomical site-specific manner. In lung metastases, tumor cell programmed death-ligand 1 (PD-L1) engages myeloid cell programmed cell death protein 1 to activate SHP2 to suppress type I interferon (IFN-I) expression to repress Cxcl9 expression to impair cytotoxic T lymphocyte (CTL) tumor recruitment. Loss of IFN-I expression thus underlies tumor immune evasion in lung metastases niche. We aimed at testing the hypothesis that forcing tumor cells to express IFNα2 activates Cxcl9 expression to increase CTL tumor recruitment to suppress lung metastasis.Methods Codon usage-optimized IFNα2-encoding DNA was designed and cloned to plasmid. IFNα2-encoding messenger RNA (mRNA) was synthesized. The plasmid DNA and mRNA were encapsulated into DOTAP (N-[1-(2,3-Dioleoyloxy)propyl]-N,N,N-trimethylammonium methyl-sulfate)-cholesterol to generate lipid nanoparticle (LNP)-encapsulated mouse IFNα2 (LNP-mIFNα2), human IFNα2 plasmid, and mouse IFNα2 mRNA (LNP-mIFNα2-mRNA). Mouse breast tumor spontaneous lung metastasis, mouse melanoma experimental lung metastasis, and human colon tumor experimental lung metastasis humanized mouse models were used to determine LNP-encapsulated IFNα2-encoding plasmid and mRNA efficacy in IFNα2 expression and antitumor immunity, toxicity, and mechanism of action in vivo.Results LNP-encapsulated IFNα2-encoding plasmid primarily accumulated in tumor-bearing lungs in mice. LNP-IFNα2 therapy produces mouse IFNα2 protein in mouse tumor-bearing mice and human IFNα2 protein in human tumor-bearing humanized mice to suppress lung metastasis, respectively. Similarly, LNP-mIFNα2-mRNA therapy produces mouse IFNα2 protein and suppressed lung metastasis in tumor-bearing mice. The increased IFNα2 protein activates Cxcl9 expression and increases T cell infiltration in lung metastases. LNP-IFNα2 therapy did not induce liver toxicity and inflammatory cytokines. In human patients with cancer, IFN-I pathway activation is correlated with CXCL9 expression and T cell expansion after PD-(L)1 immune checkpoint inhibitor immunotherapy. Mechanistically, LNP-delivered IFNα2 suppresses tumor lung metastasis through upregulating Cxcl9 in tumor-bearing mice.Conclusions Our findings determine that LNP-encapsulated IFNα2-encoding plasmid DNA and mRNA are effective agents in restoring IFNα2 expression to activate Cxcl9 expression to enhance T cell tumor recruitment to suppress tumor lung metastasis. LNP-IFNα2 is potentially a safe and yet effective third-generation IFNα2 agent for human cancer immunotherapy to treat patients with lung metastasis.